2021
DOI: 10.1088/1755-1315/623/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of carbaryl pesticide in environment using system dynamics model

Abstract: Carbaryl, one of the carbamate insecticides are used extensively for pest control in agriculture. The chemical is highly valued for its rapid action and relatively short environmental persistence. Because of its widespread and intensive use, residues of carbaryl have the potential to contaminate the environment. This study aims to formulate a system dynamics model to simulate a degradation process of carbaryl. Since carbaryl was not readily volatilizing, this study only estimates the concentration and degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition to their rapid action and short environmental persistence, carbaryls can also potentially contaminate agricultural land and thus enter the food chain. These residues have short-term cumulative effects on aquatic animals such as Lymnaea acuminata (water fish), Danio rerio (zebra fish), plankton, and other fish (Sunaryani and Rosmalina, 2021). Carbaryl residues have detrimental effects on the environment as well as on human health.…”
Section: Nanobiosensors In the Detection Of Pesticidesmentioning
confidence: 99%
“…In addition to their rapid action and short environmental persistence, carbaryls can also potentially contaminate agricultural land and thus enter the food chain. These residues have short-term cumulative effects on aquatic animals such as Lymnaea acuminata (water fish), Danio rerio (zebra fish), plankton, and other fish (Sunaryani and Rosmalina, 2021). Carbaryl residues have detrimental effects on the environment as well as on human health.…”
Section: Nanobiosensors In the Detection Of Pesticidesmentioning
confidence: 99%
“…Kerle et al (2007) also reported that mobility of pesticides in the environment is exaggerated by the sorption, solubility, vapor pressure, environmental conditions including weather, canopy, topography, ground cover and texture, organic matter, structure of soil. By modeling the occurrence of pesticide, can be a valuable way for evaluating the destiny and also the influence of pesticide in the surroundings, which may be used to find out the amount, frequency of breakdown that provides the evidence for the removal of pesticide from the environment (Sunaryani and Rosmalina, 2021;Tiryaki and Temur, 2010).…”
Section: Behavior Of Pesticides In the Environmentmentioning
confidence: 99%
“…This study aimed to predict the amount of household solid waste generation and composition, and analyze the waste management during COVID-19 in Bandung city using a system dynamics model. Modelling waste management can be a useful tool for assessing people's behavior and predicting its impact in the environment for which system dynamics model can play an important role, because in most cases, this cannot be measured directly [10]. Therefore, findings from this study provide valuable insights for people and local government to manage household solid waste, especially during and after the pandemic of COVID-19.…”
Section: Introductionmentioning
confidence: 98%